Innovative yoghurts: novel processing technologies for improving acid milk gel texture - Loveday, SM; Singh, Harjinder; Sarkar, Anwesha (Elsevier, 2013)
Consumers are demanding low-fat yoghurts without hydrocolloid stabilisers, but they are unwilling to compromise on texture for the sake of a ‘clean label’. Producing high quality low-fat yoghurt without stabilisers is challenging, and there is a need for new processing technologies to address consumer demand. Here we examine four technologies that can potentially improve the texture of yoghurt: high-pressure processing (HPP), high-pressure homogenisation (HPH), ultrasonic processing (USP) and protein crosslinking with the enzyme transglutaminase (TG). The benefits of HPH and USP depend on fat content, whilst HPP and TG work best in combination with other processes, and have strong potential for improving protein ingredients.
NOTICE: this is the author’s version of a work that was accepted for publication in Trends in Food Science and Technology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Trends in Food Science and Technology 33, 1, (2013) http://dx.doi.org/10.1016/j.tifs.2013.06.007
Keywords: Acid milk gel; Yoghurt; Rheology; High pressure processing; High-‐pressure homogenization; Transglutaminase cross linking; Ultrasonic processing